More-than-music : Echosystems, acoustemologies and histories of listening from Sápmi - Renzi, Nicola (Helsingin yliopisto, 2025)
The challenge of defining ‘music’ and ‘sound’ across cultures has been a persistent concern in ethnomusicological and anthropological research from the outset of these fields. Top-down academic applications of these concepts often remain unquestioned, affecting the rich plurality of local classifications for diverse sounding practices and experiences alongside their associated bodies of knowledge. This dissertation critically examines the relevance of these overarching categories in the context of Sámi acoustemologies, proposing a novel theoretical paradigm derived from and informed by Indigenous sound ontologies: ‘more-than-music’ (eanet go musihkka). ‘More-than-music’ seeks to challenge the ethno-anthropocentric characterizations of sonic relationships across societies and environments, which emerge from academic discourses. Its bottom-up nature underlines the necessity to acknowledge the complexity of local onto-epistemologies and the agencies of human and other-than-human beings in academic research practices. To measure the validity and applicability of the ‘more-than-music’ paradigm, this study places emphasis on juoiggus as a Sámi more-than-musical expression and biocultural heritage that bridges human performativity and aesthetics with voices of other-than-human subjectivities and animate environments. Within the scopes of this thesis, ‘more-than-music’ transcends its theoretical meanings, becoming a literal call to explore Sápmi echosystems in their biocultural complexity – from a perspective ‘beyond music’. This entails primarily a methodology of listening-with Earth, to learn from intangible sonic relationships between Sámi individuals, communities, and the land. Such approach contextually examines the desirable and undesirable quality of diverse sonic events, confronting the impacts of colonial extractivism and climate change on the delicate echosystems of the Arctic and leading to considerations of sound heritagization and sustainable practices for soundscape monitoring and preservation. The ...